(untitled) - Philip Hunter (Workingham, England, 1993)
The book includes the technical components of the LAN itself but perhaps more important embraces issues such as choice of supplier and how much help to obtain in implementing the LAN. The book also addresses the skills needed to manage a LAN effectively, which is a factor that needs to be considered in calculating how much a LAN will cost
Keywords: computer networks,data transmission systems,electronic data processing